Processing microstructure on film by femtosecond laser - Yuan, Dong-Qing; Zhou, Ming; Cai, Lan; Xu, Jian-Ting (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Selective laser patterning of thin films in a multilayer film is an emerging technology for fabrication of MEMS devices. A 775 nm Ti:sapphire laser (130 fs, 1 kHZ) was used to irradiate the thin film stacks with variations in process parameters such as feed rate and numerical aperture of objective lens. Femtosecond laser patterning of Au/Cr films which have the same thickness of about 1000 nm and are coated on glass substrate has been investiged to determine optimal parameters of the patterning process. Through a SEM and an AFM, we investigate the morphology of pattern, including the linewidth, groove depth and the laser-induced periodic surface structures (LIPSSs). The depth of the ablated groove was observed to depend on the scanning speed. And from the energy spectrum we find out which layer has been removed completely. The experimental results show that precise micromachining with desired stability and reproducibility can be achieved by controlling the ablation energy and the feed rate using appropriate numerical aperture (NA).
Optica Applicata, Vol. 39, 2009, nr 3, s. 629-635
Keywords: optyka; femtosecond laser; Au/Cr film; process; microstructure